Negative electrode material, preparation method thereof and lithium ion battery
By distributing nanosilicon in the pores of the carbon matrix of the silicon-carbon negative electrode material and using carbon dioxide to promote electrolyte dissolution, the problems of poor electrochemical performance and SEI instability are solved, and the effects of high capacity, high first efficiency and long cycle life are achieved.
Patent Information
- Application Number
- CN202311407790.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2025-04-29
AI Technical Summary
The gas molecules adsorbed in the pores of the existing silicon-carbon anode materials are difficult to dissolve in the electrolyte, resulting in poor electrochemical performance, and the initial production of carbon dioxide leads to instability of the solid electrolyte membrane (SEI).
By distributing active substances, such as nanosilicon, in the pores of the carbon matrix, and rapidly dissolving carbon dioxide in the pores of the carbon matrix into the electrolyte, the electrolyte enters the pores of the negative electrode material, while reducing the decomposition rate of vinyl fluoride carbonate, improving the stability of SEI.
It improves the capacity and first effect of the negative electrode material, enhances the lithium ion transmission efficiency, reduces the instability of SEI and the occurrence of side reactions, and extends the cycle life of the battery.
Smart Images

Figure CN119905580A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials, and in particular to negative electrode materials and preparation methods thereof, and lithium ion batteries. Background Art
[0002] At present, silicon-carbon material is one of the most advanced negative electrode materials that can achieve excellent performance of secondary batteries, such as high initial efficiency, high capacity, long cycle, and low expansion. Existing silicon-carbon negative electrode materials often have more pores, which will absorb gas molecules in the air, such as oxygen and nitrogen, during the production process. However, the solubility of these gas molecules in aqueous electrolytes is relatively low (0.031L oxygen / 0.024L nitrogen is dissolved in 1L water at 20°C standard atmospheric pressure), which leads to the electrolyte being blocked by gas molecules and difficult to fill into the pores of the negative electrode material, which seriously affects the electrochemical performance of silicon-carbon negative electrode materials.
[0003] Carbon dioxide is a large amount of greenhouse gas, and its emission has increased year by year with the progress of human industrialization, and has led to the rise of global temperature, which seriously threatens human survival. Therefore, countries around the world have successively implemented a series of carbon dioxide emission reduction measures, committed to slowing down or even eliminating the survival crisis brought about by the greenhouse effect of carbon dioxide. In the electrochemical reaction process of secondary batteries, the FEC (fluoroethylene carbonate) contained in the electrolyte will partially decompose during the lithium insertion process to produce CO2, and at the same time produce solid decomposition products (for example, LiF, -CHF-OCO2 type compounds, etc.), and form LiF-dominated SEI and "adhesion effect", so the generation of CO2 is conducive to the absorption of electrolyte by negative electrode materials. However, the initial generation of CO2 is often fast, which leads to loose and irregular SEI and even cracks, which in turn affects the initial effect and capacity of silicon-carbon negative electrode materials. Summary of the invention
[0004] The purpose of the present application is to provide a negative electrode material and a preparation method thereof, and a lithium-ion battery. The carbon dioxide in the pores of the carbon matrix in the negative electrode material of the present application can be quickly dissolved in the electrolyte and promote the electrolyte to enter the pores of the negative electrode material. At the same time, during the lithium insertion process, the dissolved carbon dioxide can reduce the decomposition rate of fluoroethylene carbonate (FEC), reduce the formation of loose and irregular SEI film, increase the bonding effect of fluorine in the lithium fluoride SEI film and lithium in the lithium silicon alloy, thereby improving the capacity and initial efficiency of the negative electrode material.
[0005] In a first aspect, the present application provides a negative electrode material, the negative electrode material comprising a carbon matrix and an active substance, the carbon matrix having pores, and the active substance being distributed in the pores of the carbon matrix;
[0006] In the infrared spectrum of the negative electrode material, the negative electrode material has a wavelength of 2375±1cm-1 The peak with the first absorption peak at 2394±1cm -1 The first absorption peak is located at a trough, the trough position is recorded as A0; and the negative electrode material is at 2919±1cm -1 The peak with the second absorption peak at 2821±1cm -1 The trough with the second absorption peak is at B0;
[0007] The negative electrode material has a carbon dioxide adsorption index P, wherein P=(A1-A0) / (B1-B0), and 0.25≤P≤0.70.
[0008] In some embodiments, the carbon matrix comprises porous carbon.
[0009] In some embodiments, the active material includes nano-silicon.
[0010] In some embodiments, the active material includes nano-silicon, and the nano-silicon includes crystalline silicon and / or amorphous silicon.
[0011] In some embodiments, the average particle size of the carbon matrix is 8 μm to 15 μm.
[0012] In some embodiments, the mass content of carbon in the negative electrode material is 49% to 51%.
[0013] In some embodiments, the mass content of the active substance in the negative electrode material is 45% to 50%.
[0014] In some embodiments, the negative electrode material contains oxygen, and the mass content of the oxygen in the negative electrode material is 1.0% to 4%.
[0015] In some embodiments, the average particle size of the negative electrode material is in the range of 0.8 μm to 25 μm.
[0016] In some embodiments, the specific surface area of the negative electrode material is 1 m 2 / g~300m 2 / g.
[0017] In some embodiments, the negative electrode material has pores, and the pores in the negative electrode material include micropores, mesopores, and macropores.
[0018] In some embodiments, the average pore size of the pores in the negative electrode material is 1 nm to 10 nm.
[0019] In some embodiments, the total pore volume of the negative electrode material is 0.001 cm 3 / g~0.20cm3 / g.
[0020] In some embodiments, the negative electrode material has pores, the pores in the negative electrode material include micropores, and the volume of the micropores accounts for 30% to 65% of the total pore volume of all pores.
[0021] In some embodiments, the negative electrode material has pores, the pores in the negative electrode material include mesopores, and the volume of the mesopores accounts for 35% to 70% of the total pore volume of all pores.
[0022] In some embodiments, the negative electrode material has pores, the pores in the negative electrode material include macropores, and the volume of the macropores accounts for 0% to 5% of the total pore volume of all pores.
[0023] In a second aspect, the present application provides a method for preparing a negative electrode material, comprising the following steps:
[0024] Providing a metal catalytic matrix, introducing a carbon source gas to deposit carbon on the metal catalytic matrix to obtain a carbon matrix having pores;
[0025] A reaction gas containing active substances is introduced and vapor deposition is performed on the carbon substrate to obtain a negative electrode material.
[0026] In some embodiments, before the carbon source gas is introduced to perform carbon deposition on the metal catalyst substrate, the method further comprises: placing the metal catalyst plate in an inert gas for air exhaust treatment.
[0027] In some embodiments, the metal in the metal catalytic matrix includes at least one of iron, nickel, copper, gold, or an alloy.
[0028] In some embodiments, the metal in the metal catalytic matrix comprises an alloy, and the alloy comprises at least one of an iron-cobalt alloy, a nickel-copper alloy, and an iron-nickel-copper alloy.
[0029] In some embodiments, the inert gas includes at least one of nitrogen, argon, and helium.
[0030] In some embodiments, the flow rate of the inert gas is 20 ccm to 200 sccm.
[0031] In some embodiments, the inert gas is introduced for a time period of 0.5 h to 3 h.
[0032] In some embodiments, after introducing a reaction gas containing active substances and performing vapor deposition on the carbon substrate, the method further comprises: sequentially repeatedly introducing a carbon source gas and a reaction gas containing active substances to perform carbon deposition and vapor deposition for 4 to 24 hours.
[0033] In some embodiments, the carbon source gas includes at least one of methane, acetylene, ethane, and propane.
[0034] In some embodiments, the flow rate of the carbon source gas is 10 sccm to 80 sccm.
[0035] In some embodiments, the carbon source gas is introduced for 5 min to 30 min.
[0036] In some embodiments, the reaction gas containing active materials includes a silicon source gas.
[0037] In some embodiments, the reaction gas containing active substances includes a silicon source gas, and the silicon source gas includes monosilane and / or disilane.
[0038] In some embodiments, the reaction gas containing active substances includes a silicon source gas, and a flow rate of the silicon source gas is 10 sccm to 80 sccm.
[0039] In some embodiments, the reaction gas containing active substances includes a silicon source gas, and the silicon source gas is introduced for a time of 5 min to 30 min.
[0040] In some embodiments, the temperature of the carbon deposition and the vapor deposition is 600°C to 700°C.
[0041] In some embodiments, the heating rate of the carbon deposition and the vapor deposition is 1° C. / min to 12° C. / min.
[0042] In some embodiments, the carbon deposition and the vapor deposition are performed under an inert gas.
[0043] In some embodiments, the carbon deposition and the vapor deposition are performed under an inert gas, and the inert gas includes at least one of nitrogen, argon, and helium.
[0044] In some embodiments, the carbon deposition and the vapor deposition are performed under an inert gas, and the flow rate of the inert gas is 5 sccm to 50 sccm.
[0045] In some embodiments, the method further comprises separating the metal catalyst matrix from the deposition product, and then sequentially subjecting the deposition product to mechanical pulverization and air flow pulverization.
[0046] In some embodiments, the mechanical crushing time is 0.5h to 3h.
[0047] In some embodiments, the air flow milling is performed for 0.5 h to 3 h.
[0048] In a third aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode material described in the first aspect or the negative electrode material prepared by the method for preparing the negative electrode material described in the second aspect.
[0049] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:
[0050] The negative electrode material provided by the present application includes a carbon matrix and an active substance, the carbon matrix has pores, and the active substance is distributed in the pores of the carbon matrix, so that the negative electrode material can maintain a higher capacity; the carbon matrix can provide a certain volume space for the expansion of the active substance, which is conducive to maintaining the structural stability of the negative electrode material, and the carbon matrix can also provide electron and ion transmission paths, improve the lithium ion transmission efficiency, and thus improve the first effect of the negative electrode material. At the same time, there is carbon dioxide gas in the pores of the carbon matrix, and the carbon dioxide gas can be quickly dissolved in the electrolyte and promote the electrolyte to enter the pores of the negative electrode material. At the same time, in the process of lithium insertion, the dissolved carbon dioxide gas can reduce the decomposition rate of fluoroethylene carbonate (FEC) in the electrolyte, reduce the formation of loose and irregular solid electrolyte membrane (SEI) on the surface of the negative electrode material, increase the bonding effect of fluorine in the lithium fluoride SEI membrane and lithium in the lithium silicon alloy, improve the interface stability of the lithium fluoride SEI, reduce the occurrence of side reactions, and reduce the consumption of active lithium ions, thereby improving the capacity and first effect of the negative electrode material.
[0051] The present application provides a method for preparing a negative electrode material. First, a carbon source gas is used to perform carbon deposition on the metal catalytic matrix to obtain a carbon matrix having pores. Then, a reaction gas containing an active substance is introduced and vapor deposition is performed on the carbon matrix. During the carbon deposition and vapor deposition processes, the metal catalytic matrix can improve the deposition efficiency, accelerate the formation of the carbon matrix and the deposition of the active substance. The active substance can be fully filled in the pores of the carbon matrix through vapor deposition, so that the prepared negative electrode material can maintain a higher capacity. At the same time, the carbon matrix can provide a certain volume space for the expansion of the active substance, which is beneficial to maintaining the structural stability of the negative electrode material. The carbon matrix can also provide electron and ion transmission paths, improve the lithium ion transmission efficiency, and thereby improve the primary effect of the negative electrode material. In addition, the pores of the carbon matrix can adsorb carbon dioxide gas. The carbon dioxide gas adsorbed in the pores of the carbon matrix can quickly dissolve in the electrolyte and promote the electrolyte to enter the pores of the negative electrode material. At the same time, during the lithium insertion process, the dissolved carbon dioxide gas can reduce the decomposition rate of fluoroethylene carbonate (FEC) in the electrolyte, reduce the formation of loose and irregular solid electrolyte membrane (SEI) on the surface of the negative electrode material, increase the adhesion effect of fluorine in the lithium fluoride SEI membrane and lithium in the lithium silicon alloy, improve the interface stability of the lithium fluoride SEI, reduce the occurrence of side reactions, and reduce the consumption of active lithium ions, thereby improving the capacity and initial efficiency of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0053] Figure 1 A schematic diagram of the structure of the negative electrode material provided in the embodiment of the present application;
[0054] Figure 2 Infrared spectra of the negative electrode materials prepared in Examples 1 to 4 of the present application;
[0055] Figure 3 The infrared spectra of the negative electrode materials prepared in Example 1 and Comparative Examples 1 to 4 of the present application;
[0056] Figure 4 This is the infrared spectra of the negative electrode materials prepared in Example 1 and Comparative Examples 5 to 8 of the present application. DETAILED DESCRIPTION
[0057] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0058] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0060] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0061] In a first aspect, the present application provides a negative electrode material, such as Figure 1 As shown, the negative electrode material includes a carbon matrix and an active substance, the carbon matrix has pores, and the active substance is distributed in the pores of the carbon matrix;
[0062] In the infrared spectrum of the negative electrode material, the negative electrode material has a wavelength of 2375±1cm -1 The peak with the first absorption peak at 2394±1cm -1 The first absorption peak is located at a trough, the trough position is recorded as A0; and the negative electrode material is at 2919±1cm -1 The peak with the second absorption peak at 2821±1cm -1 The trough with the second absorption peak is at B0;
[0063] The negative electrode material has a carbon dioxide adsorption index P, wherein P=(A1-A0) / (B1-B0), and 0.25≤P≤0.70.
[0064] The negative electrode material provided by the present application includes a carbon matrix and an active substance, the carbon matrix has pores, and the active substance is distributed in the pores of the carbon matrix, so that the negative electrode material can maintain a higher capacity; the carbon matrix can provide a certain volume space for the expansion of the active substance, which is conducive to maintaining the structural stability of the negative electrode material, and the carbon matrix can also provide electron and ion transmission paths, improve the lithium ion transmission efficiency, and thus improve the first effect of the negative electrode material. At the same time, there is carbon dioxide gas in the pores of the carbon matrix, and the carbon dioxide gas can be quickly dissolved in the electrolyte and promote the electrolyte to enter the pores of the negative electrode material. At the same time, in the process of lithium insertion, the dissolved carbon dioxide gas can reduce the decomposition rate of fluoroethylene carbonate (FEC) in the electrolyte, reduce the formation of loose and irregular solid electrolyte membrane (SEI) on the surface of the negative electrode material, increase the bonding effect of fluorine in lithium fluoride SEI and lithium in lithium silicon alloy, improve the interface stability of lithium fluoride SEI, reduce the occurrence of side reactions, and reduce the consumption of active lithium ions, thereby improving the capacity and first effect of the negative electrode material.
[0065] Specifically, the value of P can be 0.25, 0.26, 0.28, 0.30, 0.33, 0.35, 0.37, 0.40, 0.45, 0.50, 0.56, 0.60, 0.63, 0.66, 0.69 or 0.70, etc., and is not limited here.
[0066] It can be understood that the P value can represent the ability of the negative electrode material to adsorb CO2. The larger the P value, the stronger the ability of the negative electrode material to adsorb CO2, and the more CO2 adsorbed in the negative electrode material. At the same time, the ability of the negative electrode material to adsorb CO2 is related to the proportion of micropores in the negative electrode material. The more micropores there are, the stronger the ability of the negative electrode material to adsorb CO2.
[0067] When the P value is too large, it means that more CO2 is adsorbed in the negative electrode material, but it also means that there are more micropores in the negative electrode material, that is, the micropores inside the negative electrode material particles are less filled with silicon, and the silicon content in the negative electrode material is low, resulting in a low capacity of the negative electrode material. When the P value is too small, it means that less CO2 is adsorbed in the negative electrode material, but it also means that there are fewer micropores in the negative electrode material, that is, the micropores inside the negative electrode material particles are more filled with silicon, and the silicon content in the negative electrode material is high, and the capacity of the negative electrode material is increased; but the increase in the silicon content in the negative electrode material will cause the conductivity of the material particles to decrease, which in turn causes the first efficiency of the negative electrode material to decrease.
[0068] It should be noted that the values of A1-A0 represent the relative absorbance of carbon dioxide, and the values of B1-B0 represent the relative absorbance of -CH2 (carbon matrix).
[0069] In some embodiments, the carbon matrix comprises porous carbon.
[0070] In some embodiments, the active material includes nano-silicon, and the nano-silicon includes crystalline silicon and / or amorphous silicon.
[0071] In some embodiments, the average particle size of the carbon matrix is 8 μm to 15 μm, specifically 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0072] In some embodiments, the mass content of carbon element in the negative electrode material is 49% to 51%, specifically 49%, 49.3%, 49.5%, 49.6%, 49.7%, 50%, 50.2%, 50.6%, 50.7%, 50.9% or 51%, etc. Of course, it can also be other values within the above range, which is not limited here.
[0073] In some embodiments, the mass content of the active substance in the negative electrode material is 45% to 50%, specifically 45%, 45.6%, 46%, 46.8%, 47.2%, 47.9%, 48%, 48.3%, 49%, 49.3% or 50%, etc., and of course, it can also be other values within the above range, which are not limited here. It can be understood that controlling the mass content of the active substance within the above range can effectively control the volume expansion of the negative electrode material and the capacity of the negative electrode material at the same time; at the same time, since the active substance will preferentially occupy the micropores during the preparation of the negative electrode material, therefore, the mass content of the active substance is controlled within the above range, which can ensure that a certain number of micropores are retained inside the negative electrode material particles, which is conducive to the adsorption of carbon dioxide gas by the negative electrode material.
[0074] In some embodiments, the negative electrode material contains oxygen, and the mass content of the oxygen in the negative electrode material is 1.0% to 4.0%, specifically 1.0%, 1.2%, 1.3%, 1.5%, 2%, 2.1%, 2.3%, 2.5%, 3%, 3.2%, 3.5% or 4%, etc., and of course, it can also be other values within the above range, which is not limited here. In the present application, the mass content of the oxygen in the negative electrode material is controlled within the above range, which is conducive to improving the specific capacity of the negative electrode material and reducing the formation of inactive silicon dioxide.
[0075] In some embodiments, the average particle size of the negative electrode material is 0.8 μm to 25 μm, specifically 0.8 μm, 1 μm, 2 μm, 3 μm, 3.5 μm, 4 μm, 8 μm, 10 μm, 15 μm, 20 μm, 21 μm, 23 μm, 24 μm or 25 μm, etc., and of course, other values within the above range are also possible, which are not limited here. In the present application, the average particle size of the negative electrode material is controlled within the above range, which is conducive to improving the cycle performance of the lithium-ion battery made of the negative electrode material.
[0076] In some embodiments, the negative electrode material has pores, and the pores in the negative electrode material include micropores, mesopores, and macropores.
[0077] In some embodiments, the average pore size of the pores of the negative electrode material is 1 nm to 10 nm, specifically 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm, etc., and of course, other values within the above range are also possible, which are not limited here. The average pore size of the negative electrode material is controlled within the above range, which is conducive to the adsorption of CO2 by the negative electrode material.
[0078] In some embodiments, the total pore volume of the negative electrode material is 0.001 cm 3 / g~0.20cm 3 / g, specifically 0.001cm 3 / g, 0.005cm 3 / g, 0.01cm 3 / g, 0.02cm 3 / g, 0.05cm 3 / g, 0.08cm 3 / g, 0.12cm 3 / g, 0.15cm 3 / g, 0.18cm 3 / g or 0.20cm 3 / g, etc., are not limited here.
[0079] In some embodiments, the negative electrode material has pores, and the pores in the negative electrode material include micropores. The pore volume of the micropores accounts for 30% to 65% of the total pore volume of all pores, and can be specifically 30%, 35%, 40%, 50%, 55%, 58%, 60%, 62%, 63% or 65%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0080] In some embodiments, the negative electrode material has pores, and the pores in the negative electrode material include mesopores. The pore volume of the mesopores accounts for 35% to 70% of the total pore volume of all pores, and can be specifically 35%, 36%, 37%, 38%, 40%, 45%, 50%, 55%, 60%, 65% or 70%, etc. Of course, it can also be other values within the above range, which is not limited here.
[0081] In some embodiments, the negative electrode material has pores, and the pores in the negative electrode material include macropores. The pore volume of the macropores accounts for 0% to 5% of the total pore volume of all pores, and can be specifically 0%, 0.5%, 0.8%, 1%, 1.5%, 2.1%, 3.2%, 3.8%, 4.4%, 4.7% or 5%, etc., and of course it can also be other values within the above range, which is not limited here.
[0082] In some embodiments, the specific surface area of the negative electrode material is 1 m 2 / g~300m 2 / g, specifically 1m 2 / g, 5m 2 / g, 10m 2 / g, 20m 2 / g, 50m 2 / g、100m 2 / g, 125m 2 / g, 130m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g、300m 2 / g, and of course, it can also be other values within the above range, which is not limited here. Controlling the specific surface area of the negative electrode material within the above range is beneficial to improving the cycle performance of the lithium ion battery made of the negative electrode material.
[0083] In a second aspect, the present application provides a method for preparing a negative electrode material, comprising the following steps:
[0084] Step S100, providing a metal catalyst matrix, introducing a carbon source gas to deposit carbon on the metal catalyst matrix, and obtaining a carbon matrix having pores;
[0085] Step S200 , introducing a reaction gas containing active substances and performing vapor deposition on the carbon substrate to obtain a negative electrode material.
[0086] The present application provides a method for preparing a negative electrode material. First, a carbon source gas is used to perform carbon deposition on the metal catalytic matrix to obtain a carbon matrix having pores. Then, a reaction gas containing an active substance is introduced and vapor deposition is performed on the carbon matrix. During the carbon deposition and vapor deposition processes, the metal catalytic matrix can improve the deposition efficiency, accelerate the formation of the carbon matrix and the deposition of the active substance. The active substance can be fully filled in the pores of the carbon matrix through vapor deposition, so that the prepared negative electrode material can maintain a higher capacity. At the same time, the carbon matrix can provide a certain volume space for the expansion of the active substance, which is beneficial to maintaining the structural stability of the negative electrode material. The carbon matrix can also provide electron and ion transmission paths, improve the lithium ion transmission efficiency, and thereby improve the primary effect of the negative electrode material. In addition, the pores of the carbon matrix can adsorb carbon dioxide gas. The carbon dioxide gas adsorbed in the pores of the carbon matrix can quickly dissolve in the electrolyte and promote the electrolyte to enter the pores of the negative electrode material. At the same time, during the lithium insertion process, the dissolved carbon dioxide gas can reduce the decomposition rate of fluoroethylene carbonate (FEC) in the electrolyte, reduce the formation of loose and irregular solid electrolyte membrane (SEI) on the surface of the negative electrode material, increase the adhesion effect of fluorine in the lithium fluoride SEI membrane and lithium in the lithium silicon alloy, improve the interface stability of the lithium fluoride SEI, reduce the occurrence of side reactions, and reduce the consumption of active lithium ions, thereby improving the capacity and initial efficiency of the negative electrode material.
[0087] Step S100, providing a metal catalyst matrix, introducing a carbon source gas to deposit carbon on the metal catalyst matrix, and obtaining a carbon matrix having pores.
[0088] In some embodiments, before introducing the carbon source gas to perform carbon deposition on the metal catalyst substrate, the method further comprises: placing the metal catalyst plate in an inert gas for air exhaust treatment.
[0089] In some embodiments, the metal in the metal catalytic matrix includes at least one of iron, nickel, copper, gold, or an alloy.
[0090] In some embodiments, the metal in the metal catalytic matrix comprises an alloy, and the alloy comprises at least one of an iron-cobalt alloy, a nickel-copper alloy, and an iron-nickel-copper alloy.
[0091] In some embodiments, the inert gas includes at least one of nitrogen, argon, and helium.
[0092] In some embodiments, the flow rate of the inert gas is 20 sccm to 200 sccm, specifically 20 sccm, 30 sccm, 50 sccm, 80 sccm, 100 sccm, 120 sccm, 150 sccm, 180 sccm or 200 sccm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0093] In some embodiments, the inert gas introduction time is 0.5h to 3h, specifically 0.5h, 0.8h, 1h, 1.5h, 1.8h, 2h, 2.3h, 2.5h or 3h, etc. Of course, it can also be other values within the above range, which is not limited here.
[0094] In some embodiments, the carbon source gas includes at least one of methane, acetylene, ethane, and propane.
[0095] In some embodiments, the flow rate of the carbon source gas is 10 sccm to 80 sccm, specifically 10 sccm, 20 sccm, 30 sccm, 40 sccm, 50 sccm, 60 sccm, 70 sccm or 80 sccm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0096] In some embodiments, the introduction time of the carbon source gas is 5 min to 30 min, specifically 5 min, 8 min, 10 min, 15 min, 20 min, 22 min, 25 min, 28 min or 30 min, etc. Of course, it can also be other values within the above range, which is not limited here.
[0097] Step S200 , introducing a reaction gas containing active substances and performing vapor deposition on the carbon substrate to obtain a negative electrode material.
[0098] In some embodiments, the reaction gas containing active materials includes a silicon source gas.
[0099] In some embodiments, the reaction gas containing active substances includes a silicon source gas, and the silicon source gas includes monosilane and / or disilane.
[0100] In some embodiments, the reaction gas containing active substances includes a silicon source gas, and the flow rate of the silicon source gas is 10 sccm to 80 sccm, specifically 10 ccm, 20 ccm, 30 sccm, 40 sccm, 50 sccm, 60 sccm, 70 sccm or 80 sccm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0101] In some embodiments, the reaction gas containing active substances includes a silicon source gas, and the introduction time of the silicon source gas is 5 min to 30 min, specifically 5 min, 8 min, 10 min, 15 min, 20 min, 22 min, 25 min, 28 min or 30 min, etc. Of course, it can also be other values within the above range, which is not limited here.
[0102] In some embodiments, the temperature of the carbon deposition and the silicon deposition is 600°C to 700°C, specifically 600°C, 620°C, 650°C, 660°C, 680°C, 690°C or 700°C, etc., which is not limited here.
[0103] In some embodiments, the heating rate of the carbon deposition and the vapor deposition is 1°C / min to 12°C / min, specifically 1°C / min, 2°C / min, 5°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min or 12°C / min, etc. Of course, it can also be other values within the above range, which is not limited here.
[0104] In some embodiments, the carbon deposition and the vapor deposition are performed under an inert gas.
[0105] In some embodiments, the carbon deposition and the vapor deposition are performed under an inert gas, and the inert gas includes at least one of nitrogen, argon, and helium.
[0106] In some embodiments, the carbon deposition and the vapor deposition are carried out under an inert gas, and the flow rate of the inert gas is 5 sccm to 50 sccm, specifically 5 sccm, 10 sccm, 15 sccm, 20 sccm, 25 sccm, 30 sccm, 40 sccm or 50 sccm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0107] In some embodiments, after introducing a reaction gas containing active substances and performing vapor deposition on the carbon substrate, the method further includes: sequentially repeatedly introducing a carbon source gas and a reaction gas containing active substances for carbon deposition and vapor deposition for 4 h to 24 h, specifically 4 h, 8 h, 10 h, 15 h, 18 h, 20 h, 22 h or 25 h, etc., and of course other values within the above range may also be possible, which are not limited here.
[0108] In the present application, by repeatedly performing vapor deposition and carbon deposition, the deposition uniformity of the active material can be improved, the production efficiency can be increased, and the heat energy waste in the preparation process can be reduced.
[0109] In some embodiments, the method further comprises separating the metal catalyst matrix from the deposition product, and then sequentially subjecting the deposition product to mechanical pulverization and air flow pulverization.
[0110] In some embodiments, the time for mechanical crushing is 0.5h to 3h, specifically 0.5h, 0.8h, 1h, 1.5h, 1.8h, 2h, 2.4h, 2.6h or 3h. Of course, it can also be other values within the above range, which is not limited here.
[0111] In some embodiments, the time for air flow crushing is 0.5h to 3h, specifically 0.5h, 0.8h, 1h, 1.5h, 1.8h, 2h, 2.4h, 2.6h or 3h. Of course, it can also be other values within the above range, which is not limited here.
[0112] In a third aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode material described in the first aspect or the negative electrode material prepared by the method for preparing the negative electrode material described in the second aspect.
[0113] Example
[0114] Example 1
[0115] (1) Placing an iron metal catalyst plate in a tubular furnace, introducing argon gas at a flow rate of 100 sccm for 0.5 h to expel air from the tubular furnace, then adjusting the argon flow rate to 10 sccm, and starting to heat the tubular furnace at a heating rate of 10°C / min; after heating the tubular furnace to 650°C, introducing acetylene gas at a flow rate of 50 sccm for 20 min to perform carbon deposition on the iron metal catalyst plate, and then turning off the acetylene gas to obtain a carbon matrix.
[0116] (2) Then, silane gas was introduced at a flow rate of 30 sccm for 20 min to perform vapor deposition on the above carbon substrate, and then the silane gas was turned off.
[0117] (3) Repeat the above steps (1) and (2) for 8 hours, cool to room temperature, remove the iron metal catalyst plate, separate the deposited product from the iron metal catalyst plate, and perform mechanical crushing and air flow crushing on the separated silicon-carbon material for 1 hour each to obtain the negative electrode material.
[0118] The negative electrode material prepared in this embodiment includes a carbon matrix and an active substance, the carbon matrix has pores, the active substance is distributed in the pores of the carbon matrix, and the active substance includes nano-silicon.
[0119] Example 2
[0120] (1) An iron-nickel alloy metal catalyst plate is placed in a tubular furnace, and argon gas is introduced at a flow rate of 100 sccm for 0.5 h to remove the air in the tubular furnace, and then the argon flow rate is adjusted to 10 sccm, and the tubular furnace is started to be heated at a heating rate of 10°C / min; after the tubular furnace is heated to 650°C, acetylene gas is introduced at a flow rate of 50 sccm for 20 min to perform carbon deposition on the iron-nickel alloy metal catalyst plate, and then the acetylene gas is turned off to obtain a carbon matrix.
[0121] (2) Then, silane gas was introduced at a flow rate of 35 sccm for 20 min to perform vapor deposition on the above carbon substrate, and then the silane gas was turned off.
[0122] (3) Repeat the above steps (1) and (2) for 8 hours, cool to room temperature, take out the iron-nickel alloy metal catalyst plate, separate the deposited product from the iron-nickel alloy metal catalyst plate, and perform mechanical crushing and air flow crushing on the separated silicon-carbon material for 1 hour each to obtain the negative electrode material.
[0123] The negative electrode material prepared in this embodiment includes a carbon matrix and an active substance, the carbon matrix has pores, the active substance is distributed in the pores of the carbon matrix, and the active substance includes nano-silicon.
[0124] Example 3
[0125] (1) A nickel metal catalyst plate is placed in a tubular furnace, and argon gas is introduced at a flow rate of 200 sccm for 0.5 h to remove the air in the tubular furnace. Then, the argon flow rate is adjusted to 10 sccm, and the tubular furnace is started to be heated at a heating rate of 10°C / min. After the tubular furnace is heated to 650°C, acetylene gas is introduced at a flow rate of 50 sccm for 20 min to perform carbon deposition on the nickel metal catalyst plate, and then the acetylene gas is turned off to obtain a carbon matrix.
[0126] (2) Then, silane gas was introduced at a flow rate of 40 sccm for 20 minutes to perform vapor deposition on the above carbon substrate, and then the silane gas was turned off.
[0127] (3) Repeat the above steps (1) and (2) for 8 hours, cool to room temperature, remove the nickel metal catalyst plate, separate the deposited product from the nickel metal catalyst plate, and perform mechanical crushing and air flow crushing on the separated silicon-carbon material for 1 hour each to obtain the negative electrode material.
[0128] The negative electrode material prepared in this embodiment includes a carbon matrix and an active substance, the carbon matrix has pores, the active substance is distributed in the pores of the carbon matrix, and the active substance includes nano-silicon.
[0129] Example 4
[0130] (1) A copper metal catalyst plate is placed in a tubular furnace, and argon gas is introduced at a flow rate of 200 sccm for 0.5 h to remove the air in the tubular furnace. Then, the argon flow rate is adjusted to 10 sccm, and the tubular furnace is started to be heated at a heating rate of 10°C / min. After the tubular furnace is heated to 650°C, acetylene gas is introduced at a flow rate of 50 sccm for 20 min to perform carbon deposition on the copper metal catalyst plate, and then the acetylene gas is turned off to obtain a carbon matrix.
[0131] (2) Then, silane gas was introduced at a flow rate of 45 sccm for 20 minutes to perform vapor deposition on the above carbon substrate, and then the silane gas was turned off.
[0132] (3) Repeat the above steps (1) and (2) for 8 hours, cool to room temperature, remove the copper metal catalyst plate, separate the deposited product from the copper metal catalyst plate, and perform mechanical crushing and air flow crushing on the separated silicon-carbon material for 1 hour each to obtain the negative electrode material.
[0133] The negative electrode material prepared in this embodiment includes a carbon matrix and an active substance, the carbon matrix has pores, the active substance is distributed in the pores of the carbon matrix, and the active substance includes nano-silicon.
[0134] Example 5
[0135] The difference from Example 1 is that (2) silane gas is then introduced at a flow rate of 10 sccm for 30 minutes to perform vapor deposition on the above carbon substrate, and then the silane gas is turned off.
[0136] The negative electrode material prepared in this embodiment includes a carbon matrix and an active substance, the carbon matrix has pores, the active substance is distributed in the pores of the carbon matrix, and the active substance includes nano-silicon.
[0137] Example 6
[0138] The difference from Example 1 is that (2) silane gas is then introduced at a flow rate of 80 sccm for 5 min to perform vapor deposition on the carbon substrate, and then the silane gas is turned off. The negative electrode material prepared in this example includes a carbon substrate and an active substance, the carbon substrate has pores, the active substance is distributed in the pores of the carbon substrate, and the active substance includes nano-silicon.
[0139] Comparative Example 1
[0140] The negative electrode material prepared in Example 1 was used to carry out a polyfluoropolymer pore blocking experiment, and the specific steps are as follows:
[0141] (1) 30 g of the negative electrode material prepared in Example 1, 1 g of acrylic acid, 2 g of polypropylene pyrrolidone and 300 mL of n-butanol were placed in a reaction bottle, and nitrogen was introduced after evacuation to ensure that the reaction environment was a nitrogen environment.
[0142] (2) The reaction bottle was placed in a magnetic stirring water bath, stirred and heated to 65°C, and then 1 g of azobisisobutyronitrile and 20 mL of cyclopentane were added and kept at the constant temperature for 0.5 h. Subsequently, 1 g of hexafluorobutyl acrylate and 20 mL of acetone were added and kept at the constant temperature for 0.5 h. The reaction solution was then heated to 70°C and kept at the constant temperature for 6 h to terminate the reaction. Finally, the fluoropolymer pore-blocking comparison negative electrode material 1 was obtained after filtration and ethanol washing.
[0143] Comparative Example 2
[0144] Different from Comparative Example 1, (2) the reaction bottle was placed in a magnetic stirring water bath, stirred and heated to 65°C, and then 1g of azobisisobutyronitrile and 20mL of cyclopentane were added and kept at a constant temperature for 0.5h, followed by adding 2g of hexafluorobutyl acrylate and 20mL of acetone and keeping the temperature constant for 0.5h, and then the reaction solution was heated to 70°C and kept at a constant temperature for 6h to terminate the reaction, and finally, after filtration and ethanol washing, the comparative negative electrode material 2 with fluoropolymer plugging was obtained.
[0145] Comparative Example 3
[0146] Different from Comparative Example 1, (2) the reaction bottle was placed in a magnetic stirring water bath, stirred and heated to 65°C, and then 2g of azobisisobutyronitrile and 20mL of cyclopentane were added and kept at a constant temperature for 0.5h, followed by adding 2g of hexafluorobutyl acrylate and 20mL of acetone and keeping the temperature constant for 0.5h, and then the reaction solution was heated to 70°C and kept at a constant temperature for 6h to terminate the reaction, and finally, after filtration and ethanol washing, the fluoropolymer pore-blocking comparative negative electrode material 3 was obtained.
[0147] Comparative Example 4
[0148] The silicon-carbon negative electrode active material prepared in Example 1 was used to carry out a silicon-free porous carbon preparation experiment, and the specific steps are as follows:
[0149] 30 g of the negative electrode material prepared in Example 1 was placed in 250 mL of a 20% by mass hydrofluoric acid solution, and after soaking for 12 hours, the solution was filtered and washed with pure water to obtain a comparative porous carbon negative electrode active material 4.
[0150] Comparative Example 5
[0151] The silicon-carbon negative electrode active material prepared in Example 1 was used to carry out a carbon growth pore blocking experiment, and the specific steps are as follows:
[0152] (1) 30 g of the negative electrode material prepared in Example 1 was placed in a tube furnace, and argon gas was introduced at a flow rate of 100 sccm for 0.5 h to exclude air. The argon flow rate was then adjusted to 10 sccm, and the tube furnace was heated at a heating rate of 10°C / min to 650°C.
[0153] (2) Then, acetylene gas was introduced at a flow rate of 10 sccm for 10 min, and the acetylene gas was turned off and the temperature was naturally lowered to room temperature to obtain comparative negative electrode material 5.
[0154] Comparative Example 6
[0155] Different from comparative example 5, (2) acetylene gas was then introduced at a flow rate of 10 sccm for 20 min, the acetylene gas was turned off, and the temperature was naturally lowered to room temperature to obtain comparative negative electrode material 6.
[0156] Comparative Example 7
[0157] Different from comparative example 5, (2) acetylene gas was then introduced at a flow rate of 10 sccm for 30 min, the acetylene gas was turned off, and the temperature was naturally lowered to room temperature to obtain comparative negative electrode material 7.
[0158] Comparative Example 8
[0159] Different from comparative example 5, (2) acetylene gas was then introduced at a flow rate of 10 sccm for 40 min, the acetylene gas was turned off, and the temperature was naturally lowered to room temperature to obtain comparative negative electrode material 8.
[0160] Test Method
[0161] (1) Testing method for carbon mass content in negative electrode materials:
[0162] The sample is burned in a high-temperature, oxygen-rich state using the German Bruker / German Airt infrared carbon and sulfur analyzer G4 ICARUS HF / CS-i. The carbon element it contains is oxidized into carbon dioxide and enters the infrared detector with the carrier gas. The mass content of the carbon element is calculated by quantitatively analyzing the changes in the intensity of the infrared absorption wavelength of the carbon dioxide signal.
[0163] (2) Test method for the mass content of active substances in negative electrode materials:
[0164] After drying the sample overnight, place it in a corundum crucible, and place the crucible in a muffle furnace (Nanyang Xinyu SA2-9-17TP) at 1200°C for 480 minutes to complete the combustion of carbon and the oxidation reaction of silicon or silicon oxide to silicon dioxide. During the process, the crucible weight m0, sample weight m1, and total weight of the crucible and product after calcination m2 were recorded, and the silicon content was calculated according to the following formula: Si% = (m2-m0) / m1×28.09 / 60.09×100%.
[0165] (3) Test method for the mass content of oxygen in negative electrode materials:
[0166] The German Förder oxygen, nitrogen and hydrogen element analyzer ONH 2000 was used. The sample was wrapped in flux and melted in an inert atmosphere. The oxygen element contained in the sample was reduced to carbon dioxide by the carbon in the graphite crucible. The generated carbon dioxide entered the infrared detector with the carrier gas, and the mass content of the oxygen element was calculated by quantitative statistics of the changes in the carbon dioxide infrared signal.
[0167] (4) Test method for particle size of negative electrode material:
[0168] Malvern Laser Particle Sizer MS3000 is used. Based on the principle that the intensity distribution of scattered light generated by particles in all directions depends on the size of the particles, large particles have small scattering angles and small particles have large scattering angles, the particle size distribution of the particles can be obtained by using the scattered light intensity distribution of laser diffraction.
[0169] (5) Infrared spectrum test method for negative electrode materials:
[0170] A small amount of test sample and KBr pellets were tested using the American Fourier infrared spectrometer Thermo Scientific iN10 to obtain their infrared absorption spectra.
[0171] (6) Testing method for average pore diameter:
[0172] The iPore620 pore size tester and BET pore size distribution test method were used to test the isothermal adsorption characteristic curve of nitrogen. The pore size distribution data of the material was obtained through DFT simulation analysis, and then the average pore size, total pore volume and BET specific surface area of the material were obtained.
[0173] (7) Electrochemical performance test:
[0174] The negative electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 8, conductive carbon black (super P) and LA133 were mixed into a slurry at a ratio of 70:15:15 and evenly coated on a copper foil, and dried to prepare a negative electrode sheet. A metal lithium sheet was used as a counter electrode, and button cells were assembled in a glove box filled with argon gas, and their charging capacity and coulomb efficiency were tested on a Blue Electric Battery Test Cabinet M340A.
[0175] The above test data are detailed in Table 1 and Table 2.
[0176] Table 1 Performance parameters of negative electrode materials prepared in various embodiments and comparative examples
[0177]
[0178]
[0179] Table 1 Electrochemical performance parameters of negative electrode materials prepared in various embodiments and comparative examples
[0180] First effect% Charging capacity mAh / g Example 1 92.8 1942 Example 2 93.2 2083 Example 3 92.4 2276 Example 4 91.4 2330 Example 5 91.7 1703 Example 6 92.1 1804 Comparative Example 1 87.6 1854 Comparative Example 2 86.9 1854 Comparative Example 3 86.2 1782 Comparative Example 4 40.3 342 Comparative Example 5 87.7 1872 Comparative Example 6 87.1 1812 Comparative Example 7 86.4 1789 Comparative Example 8 85.2 1753
[0181] According to the test data in Table 1 and Table 2, the negative electrode materials prepared in Examples 1 to 6 include a carbon matrix and an active substance, the carbon matrix has pores, and the active substance is distributed in the pores of the carbon matrix, so that the negative electrode material can maintain a higher capacity; the carbon matrix can provide a certain volume space for the expansion of the active substance, which is conducive to maintaining the structural stability of the negative electrode material. The carbon matrix can also provide electron and ion transmission paths, improve the lithium ion transmission efficiency, and thus improve the first effect of the negative electrode material. At the same time, there is CO2 in the pores of the carbon matrix, CO2 can be quickly dissolved in the electrolyte, and promote the electrolyte to enter the pores of the negative electrode material. At the same time, in the process of lithium insertion, the dissolved CO2 can reduce the decomposition rate of fluoroethylene carbonate (FEC), reduce the formation of loose and irregular solid electrolyte membrane (SEI), increase the bonding effect of fluorine in the lithium fluoride SEI membrane and lithium in the lithium silicon alloy, improve the interface stability of the lithium fluoride SEI membrane, reduce the occurrence of side reactions, and reduce the consumption of active lithium ions, thereby improving the capacity and first effect of the negative electrode material.
[0182] Figure 2 The infrared spectra of the negative electrode materials prepared in Examples 1 to 4 are as follows: Figure 2 As shown in Table 1, as the mass content of nano-silicon gradually increases in the negative electrode materials of Examples 1 to 4, the carbon dioxide adsorption index P value of the negative electrode materials decreases, and the amount of carbon dioxide adsorbed in the negative electrode materials decreases. This is because in the preparation process of the negative electrode material, nano-silicon will preferentially occupy the micropores. As the mass content of nano-silicon increases, the micropores in the negative electrode material are filled, the proportion of micropores in the negative electrode material decreases, and the proportion of mesopores and macropores increases, resulting in an increase in the average pore size of the negative electrode material. At the same time, as the mass content of the filled nano-silicon increases, the total pore volume, BET specific surface area and oxygen content of the negative electrode material also gradually decrease. The selective adsorption of carbon dioxide is often related to the size of the pore size and the functional groups on the pore surface. Small pores and functional groups that can form hydrogen bonds with carbon dioxide are often conducive to the adsorption of carbon dioxide. As the silicon content increases, the pore size of the negative electrode material increases, and the oxygen-containing functional groups such as the -OH group on the pore surface are shielded, resulting in a weakening of the ability of the negative electrode material to adsorb carbon dioxide. The 2375cm -1 The infrared absorption peak at also weakens (from a double peak to a single peak, or even disappears), and the calculated carbon dioxide adsorption index P also gradually decreases.
[0183] Figure 3 The infrared spectra of the negative electrode materials prepared in Example 1 and Comparative Examples 1 to 4 are as follows: Figure 3As shown in Table 1, in Comparative Examples 1 to 3, as the amount of pore-blocking fluoropolymer increases, the average pore size increases and the total pore volume decreases because the micropores have a larger surface energy and will be blocked first, which leads to a significant decrease in the carbon dioxide adsorption index P. Although the pore-blocking fluoropolymer can introduce more oxygen-containing functional groups, the excessive reduction in the total pore volume leaves no room for the adsorption of carbon dioxide, thereby reducing the amount of carbon dioxide adsorbed in the negative electrode material. Comparative Example 4 is a silicon-free porous carbon with a large total pore volume and a high oxygen content, but its adsorption of carbon dioxide is negligible. This is because its pore size is too large and it loses its selective adsorption capacity for carbon dioxide. The oxygen-containing functional groups produced by the higher oxygen content may be competitively adsorbed by water molecules without pore size restrictions, thereby resulting in the loss of its carbon dioxide adsorption capacity.
[0184] Figure 4 The infrared spectra of the negative electrode materials prepared in Example 1 and Comparative Examples 5 to 8 are as follows: Figure 4 As shown in Table 1, in Comparative Examples 5 to 8, as the amount of carbon deposition coating increases, the micropores in the negative electrode material are occupied by carbon deposition, resulting in an increase in the average pore size and a gradual decrease in the total pore volume. At the same time, the porous silicon carbon is reduced by the carbon source, and the oxygen on the silicon carbon is converted into carbon monoxide or carbon dioxide and lost with the airflow or covered by the deposited carbon, which leads to a significant reduction in the oxygen-containing functional groups on the pore surface. The increase in pore size, the decrease in total pore volume and oxygen content together cause the negative electrode material to have a reduced carbon dioxide adsorption capacity, which reduces the amount of carbon dioxide adsorbed in the negative electrode material, resulting in a weakened adsorption capacity of the pores of the negative electrode material for the electrolyte. At the same time, during the lithium insertion process, due to the reduction in dissolved CO2, the decomposition rate of fluoroethylene carbonate (FEC) is weakened, which increases the formation of loose and irregular SEI films, weakens the bonding effect of fluorine in the lithium fluoride SEI film and lithium in the lithium silicon alloy, reduces the interfacial stability of the lithium fluoride SEI film, increases the occurrence of side reactions, and increases the consumption of active lithium ions, thereby reducing the capacity and first efficiency of the negative electrode material.
[0185] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A negative electrode material, characterized in that: The negative electrode material includes a carbon matrix and an active substance, the carbon matrix has pores, and at least part of the active substance is distributed in the pores of the carbon matrix; In the infrared spectrum of the negative electrode material, the negative electrode material has a wavelength of 2375±1cm -1 The peak with the first absorption peak at 2394±1cm -1 The first absorption peak is located at a trough, the trough position is recorded as A0; and the negative electrode material is at 2919±1cm -1 The peak with the second absorption peak at 2821±1cm -1 The trough with the second absorption peak is at B0; The negative electrode material has a carbon dioxide adsorption index P, wherein P=(A1-A0) / (B1-B0), and 0.25≤P≤0.
70.
2. The negative electrode material according to claim 1, characterized in that The negative electrode material meets at least one of the following characteristics: (1) The carbon matrix includes porous carbon; (2) The average particle size of the carbon matrix is 8 μm to 15 μm; (3) The active material includes nano-silicon; (4) The active material includes nano-silicon, and the nano-silicon includes crystalline silicon and / or amorphous silicon.
3. The negative electrode material according to claim 1, characterized in that The negative electrode material meets at least one of the following characteristics: (1) The mass content of carbon in the negative electrode material is 49% to 51%; (2) The mass content of the active substance in the negative electrode material is 45% to 50%; (3) The negative electrode material contains oxygen, and the mass content of the oxygen in the negative electrode material is 1.0% to 4.0%; (4) The average particle size of the negative electrode material is in the range of 0.8 μm to 25 μm; (5) The specific surface area of the negative electrode material is 1 m 2 / g~300m 2 / g; (6) The negative electrode material has pores, and the pores in the negative electrode material include micropores, mesopores and macropores; (7) The average pore size of the pores in the negative electrode material is 1 nm to 10 nm; (8) The total pore volume of the negative electrode material is 0.001 cm 3 / g~0.20cm 3 / g; (9) The negative electrode material has pores, the pores in the negative electrode material include micropores, and the volume of the micropores accounts for 30% to 65% of the total pore volume of all pores; (10) The negative electrode material has pores, the pores in the negative electrode material include mesopores, and the volume of the mesopores accounts for 35% to 70% of the total pore volume of all pores; (11) The negative electrode material has pores, the pores in the negative electrode material include macropores, and the volume of the macropores accounts for 0% to 5% of the total pore volume of all pores.
4. A method for preparing a negative electrode material, characterized in that: The following steps are involved: Providing a metal catalytic matrix, introducing a carbon source gas to deposit carbon on the metal catalytic matrix to obtain a carbon matrix having pores; A reaction gas containing active substances is introduced and vapor deposition is performed on the carbon substrate to obtain a negative electrode material.
5. The preparation method according to claim 4, characterized in that: Before the carbon source gas is introduced to perform carbon deposition on the metal catalyst substrate, the method further comprises: placing the metal catalyst substrate in an inert gas for exhaust treatment.
6. The preparation method according to claim 5, characterized in that: The method comprises at least one of the following technical features: (1) The metal in the metal catalyst matrix includes at least one of iron, nickel, copper, gold or an alloy; (2) The metal in the metal catalyst matrix includes an alloy, and the alloy includes at least one of an iron-cobalt alloy, a nickel-copper alloy, and an iron-nickel-copper alloy; (3) The inert gas includes at least one of nitrogen, argon and helium; (4) The flow rate of the inert gas is 20 ccm to 200 sccm; (5) The inert gas is introduced for 0.5 h to 3 h.
7. The preparation method according to claim 4, characterized in that: After introducing the reaction gas containing active substances and performing vapor deposition on the carbon substrate, the method further comprises: repeatedly introducing the carbon source gas and the reaction gas containing active substances in sequence to perform carbon deposition and vapor deposition for 4 hours to 24 hours.
8. The preparation method according to claim 4, characterized in that: The method comprises at least one of the following technical features: (1) The carbon source gas includes at least one of methane, acetylene, ethane and propane; (2) The flow rate of the carbon source gas is 10 sccm to 80 sccm; (3) The carbon source gas is introduced for 5 to 30 minutes; (4) The reaction gas containing active substances includes silicon source gas; (5) The reactive gas containing active substances includes a silicon source gas, and the silicon source gas includes monosilane and / or disilane; (6) The reaction gas containing the active substance includes a silicon source gas, and the flow rate of the silicon source gas is 10 sccm to 80 sccm; (7) The reactive gas containing active substances includes a silicon source gas, and the introduction time of the silicon source gas is 5 min to 30 min; (8) The temperature of the carbon deposition and the vapor deposition is 600° C. to 700° C.; (9) The heating rate of the carbon deposition and the vapor deposition is 1°C / min to 12°C / min; (10) The carbon deposition and the vapor deposition are performed under an inert gas; (11) The carbon deposition and the vapor deposition are performed under an inert gas, wherein the inert gas includes at least one of nitrogen, argon, and helium; (12) The carbon deposition and the vapor deposition are performed under an inert gas, and the flow rate of the inert gas is 5 sccm to 50 sccm.
9. The preparation method according to claim 4, characterized in that: The method further comprises separating the metal catalyst matrix from the deposited product, and then sequentially subjecting the deposited product to mechanical pulverization and air flow pulverization, which satisfies at least one of the following technical features: (1) The mechanical crushing time is 0.5h to 3h; (2) The time for the air flow crushing is 0.5h to 3h.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode material according to any one of claims 1 to 3 or the negative electrode material prepared by the method for preparing the negative electrode material according to any one of claims 4 to 9.
Citation Information
Cited By
Negative electrode material and preparation method therefor, and lithium-ion battery
EP4636869A1